2018
DOI: 10.1002/jcp.27469
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor‐2 inhibits CD40‐mediated periodontal inflammation

Abstract: Fibroblast growth factor-2 (FGF-2) stimulates periodontal regeneration by a broad spectrum of effects on periodontal ligament (PDL) cells, such as proliferation, migration, and production of extracellular matrix. A critical factor in the success of periodontal regeneration is the rapid resolution of inflammatory responses in the tissue. We explored an anti-inflammatory effect of FGF-2 during periodontal regeneration and healing. We found that FGF-2 on mouse periodontal ligament cells (MPDL22) markedly downregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…As a well-known growth factor, bFGF regulates the proliferation, apoptosis, and regeneration of several cells/tissues, including gingiva and periodontal ligament [96,97]. More recently, it was reported that bFGF inhibits periodontal inflammation by suppressing CD40-mediated inflammatory signaling [98]. Based on the regenerative capacity of bFGF, many clinical trials were already performed to recuperate periodontal tissue which was disrupted by age or pathological conditions.…”
Section: Othersmentioning
confidence: 99%
“…As a well-known growth factor, bFGF regulates the proliferation, apoptosis, and regeneration of several cells/tissues, including gingiva and periodontal ligament [96,97]. More recently, it was reported that bFGF inhibits periodontal inflammation by suppressing CD40-mediated inflammatory signaling [98]. Based on the regenerative capacity of bFGF, many clinical trials were already performed to recuperate periodontal tissue which was disrupted by age or pathological conditions.…”
Section: Othersmentioning
confidence: 99%
“…FGF2 is the most studied growth factor of the FGF family that is expressed in many tissues and body fluids, including the tears and saliva [ 29 ]. It induces periodontal regeneration and suppresses inflammation indicating its role in regeneration and healing [ 30 ]. In this study, FGF5 was also identified, which has the same effect on growth/differentiation balance of PDL cells, and is expressed in large amounts in PDL cell culture [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of FGF signalling by exogenous FGF2 may regulate NF-kB because of the suppressive effect of FGF2 on inflammation (22). Thus, we investigated the relationship between phosphorylated RelA and FGF2 stimulation.…”
Section: Discussionmentioning
confidence: 99%